European Data Protection: Coming of Age - Gutwirth, Serge (Springer, 2013)
On 25 January 2012, the European Commission presented its long awaited new “Data protection package”. With this proposal for a drastic revision of the data protection framework in Europe, it is fair to say that we are witnessing a rebirth of European data protection, and perhaps, its passage from an impulsive youth to a more mature state. Technology advances rapidly and mobile devices are significantly changing the landscape. Increasingly, we carry powerful, connected, devices, whose location and activities can be monitored by various stakeholders. Very powerful social network sites emerged in the first half of last decade, processing personal data of many millions of users. Updating the regulatory framework was imminent and the presentation of the new package will initiate a period of intense debate in which the proposals will be thoroughly commented upon and criticized, and numerous amendments will undoubtedly be proposed. This volume brings together some 19 chapters offering conceptual analyses, highlighting issues, proposing solutions, and discussing practices regarding privacy and data protection. In the first part of the book, conceptual analyses of concepts such as privacy and anonymity are provided. The second section focuses on the contrasted positions of digital natives and ageing users in the information society. The third section provides four chapters on privacy by design, including discussions on roadmapping and concrete techniques. The fourth section is devoted to surveillance and profiling, with illustrations from the domain of smart metering, self-surveillance and the benefits and risks of profiling. The book concludes with case studies pertaining to communicating privacy in organisations, the fate of a data protection supervisor in one of the EU member states and data protection in social network sites and online media.